Incidence and Factors Predicting Respiratory Complications After 48 Hours of General Anesthesia - Chokmoh, Khanarut; Saensom, Donwiwat (Nursing Science Journal of Thailand, 2022)
Purpose: This study was conducted to assess the incidence rate of post-general anesthesia respiratory complications (P-GARCs) and the predicting factors at 48 hours after general anesthesia (GA). Design: Analytical prospective cohort study. Methods: Subjects were 322 patients aged 18 years and older who received an operation under GA. and 8 nurse anesthetists in one secondary care-level hospital. The P-GARCs predicting factors assessment form, a nurse anesthetist competency checklist and a nurse anesthetist’s adherence to anesthesia guideline checklist were used for data collection. Data were analyzed using descriptive statistics and cox proportional hazards regressions. Main finding: Results revealed that 32 patients developed P-GARCs at 48 hours after GA with an incidence rate of 2.29 events/1000-hours of GA. Unmodifiable predictors of P-GARCs included age (HR = 1.04, 95%CI = 1.01, 1.06), having an emergency operation (HR = 2.41, 95%CI = 1.06, 5.47) and duration of intubation (HR = 1.00, 95%CI = .99, หน1.01). Modifiable predictors included body mass index (HR = 1.16, 95%CI = 1.06, 1.26), smoking (HR = 6.03, 95%CI = 2.34, 15.54) and number of intubation (HR = 11.83, 95%CI = 1.17, 119.8). Protective factor against P-GARCs was nurse anesthetist’s adherence to anesthesia guideline (HR = .94, 95%CI = .90, .98). Conclusion and recommendations: Predicting factors of P-GARCs included both modifiable and unmodifiable factors. As a result, the modifiable factors should be manipulated to effectively prevent the P-GARCs and nurse anesthetists should be encouraged to strictly adhere to the anesthesia guideline. For unmodifiable factors, prevention and surveillance of G-PARCs should be focused among patients with these factors.